PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU - Harmendi, Muhammad; Lian, Bukman; Wardarita, Ratu (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to determine the effect of principal leadership style and work motivation on teacher performance of Muhammadiyah junior high schools and islamic junior high school in Palembang City. This research is a quantitative research. The subjects of this study were the principal and teachers. Data collection methods using questionnaires and documentation. Test instrument using validity test and reliability test. Data analysis used descriptive and inferential data analysis techniques. The results showed: (1) the leadership style of the principal has a significant effect on the performance of teachers SMP and MTS Muhammadiyah in Palembang City; (2) work motivation has a significant effect on the performance of teachers SMP and MTS Muhammadiyah in Palembang City. (3) the principal’s leadership style and work motivation jointly influence the performance of teachers SMP and MTS Muhammadiyah in Palembang City.